Effects of Training Side Hop Over Barrier With Dumbell and Hexagon With Dumbell On Leg Strength and Leg Power - Nur Akbari; Oce Wiriawan; Nining Widyah Kusnanik (Journal of Sport Science and Education, 2018)
This study was conducted at 45 students of SMAN 1 Cerme with aged between 15-16 years old. Students were  divided into 3 groups. the type of research used quantitative with quasi-experimental approach. Instruments of this study were test of leg strength and leg power using Leg Dynamometer and  Jump MD. The research design used matching only design. Data was anlyzed using ANOVA. The results of the  research was found that training program side hop over  barrier with dumbell and hexagon with  dumbbell significantly increase at leg strength and leg power (Sig. 0.000 <Î± = 0.05). Group I, Group II and Group III had significant difference (Sig. 0.000 Î± = 0.005). Percentage increase in leg strength group 1 of 1,80% and leg  power of 15,49%. Percentage increase in leg strength group II of  1,68% and a power of 14,27% and whereas in the control group increase in leg strength was 1.67% power at 12.32%.It can be concluded that There was an increase in leg strength and leg power in each group after the training was given. In addition, there were differences among the three groups effects seen improved in leg strength and leg power through ANOVA, where the training side hop over barrier with dumbbell and hexagon with dumbell had increased in leg strength and leg   power. But side hop over barrier with dumbbell had more significant increased than hexagon with dumbbell. Key words: Side hop over with barrier dumbell,  hexagon with dumbell, leg strength and leg power.